Workshop Peningkatan Kompetensi Guru-Guru Bahasa Inggris Sekolah Menengah Pertama (SMP) dikota Palangka Raya - Sulistyowati; Norhayati; Haris, Ferdiyani; Rosmiati; Sam'ani; Jayanti, Sherly; Santoso Pakpahan, Herman; Suparno; Ichsan, Mochammad (LPPM Universitas Harapan Bangsa Purwokerto, 2024)
This community service activity, which is a form of higher education tridharma obligation, aims to increase the professionalism and competence of teachers/teachers at the Junior High School (SMP) level in the city of Palangka Raya. The material presented in this community service activity is in the form of various interactive and interesting learning methods in teaching in English and making interactive learning media with the Microsoft PowerPoint application. This service activity was carried out on Saturday, February 03, 2024 at the STMIK Palangkaraya campus hall. The target of this community service activity is the teachers/teachers of Junior High Schools (SMP) in the city of Palangka Raya. The method of this activity uses the form of presentations and training which are then followed by discussions between participants and presenters. The costs for this community service activity are fully sourced from STMIK Palangkaraya through the Research, Publication and Community Service Unit (UP3M). The results of this community service can be concluded that the activity participants gained additional knowledge to further enhance their respective professionalism and competence